The effect of earnings management upon the investment efficiency using the company size as the variable of moderated agent (Empirics study at the companies registered at the Indonesia stock exchange 2014 – 2018) - Syarief Gerald Prasetya (The Accounting Journal of Binaniaga, 2020)
This study aims to determine the effect of earnings management on investment efficiency and determine the effect of company size on the relationship between earnings management and investment efficiency, (group of companies overinvestment and underinvestment). This research is a quantitative study using descriptive statistical analysis methods and Moderated Regression Analysis (MRA). The data used are financial data of companies listed on the IDX instead of the financial industry. The results showed that earnings management had affected the efficiency of investment both overinvestment and underinvestment companies. Inspited of that, it has figured out that company size is a mediator variable which means that company size influences the relationship between earnings management and investment efficiency. The strength of the relationship between earnings management and investment efficiency is determined by the size of the company. Keywords: Earnings Management, Investment Efficiency, Company Size